Perbandingan Administrasi Negara Indonesia Dengan Malaysia - Nikmah, Rismatun (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Public administration plays a crucial role in ensuring effective governance and the delivery of public services. Differences in administrative systems among countries influence policy implementation and bureaucratic performance. Indonesia and Malaysia, as neighboring countries in Southeast Asia, share certain historical and socio-cultural similarities but apply different systems of state administration. This study aims to compare the state administration systems of Indonesia and Malaysia by examining bureaucratic structure, public service delivery, and administrative reform. This research employs a qualitative approach using a comparative study method. Data were collected through literature review of scientific journals, books, and official government documents from both countries. The results show that Indonesia adopts a decentralized administrative system with a presidential form of government, while Malaysia implements a more centralized administrative system within a federal parliamentary framework. These differences affect bureaucratic coordination, efficiency, and public service implementation. In conclusion, both countries have strengths and weaknesses in their administrative systems, and comparative analysis can provide valuable insights for improving state administration in Indonesia. ABSTRACT Administrasi negara memiliki peran penting dalam penyelenggaraan pemerintahan dan pelayanan publik. Perbedaan sistem administrasi antarnegara berpengaruh terhadap pelaksanaan kebijakan dan kinerja birokrasi. Indonesia dan Malaysia sebagai negara bertetangga di kawasan Asia Tenggara memiliki kesamaan historis dan sosial budaya, namun menerapkan sistem administrasi negara yang berbeda. Penelitian ini bertujuan untuk membandingkan administrasi negara Indonesia dan Malaysia dengan meninjau struktur birokrasi, sistem pelayanan publik, serta pelaksanaan reformasi administrasi. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi komparatif. Data dikumpulkan melalui studi literatur terhadap jurnal ilmiah, buku, serta dokumen resmi pemerintah dari kedua negara. Hasil penelitian menunjukkan bahwa Indonesia menerapkan sistem administrasi negara yang terdesentralisasi dengan bentuk pemerintahan presidensial, sedangkan Malaysia cenderung menerapkan sistem administrasi yang lebih terpusat dalam kerangka pemerintahan parlementer federal. Perbedaan tersebut memengaruhi koordinasi birokrasi, efisiensi, dan pelaksanaan pelayanan publik. Kesimpulannya, masing-masing negara memiliki kelebihan dan kelemahan dalam sistem administrasi negaranya, sehingga studi perbandingan dapat menjadi bahan evaluasi bagi peningkatan administrasi negara di Indonesia